O papel do laboratório áudio-visual na Universidade - Breton, Jean Marie (Semina: Ciências Exatas e Tecnológicas, 2004)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0pt; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 85.05pt 70.85pt 85.05pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> This paper tries to determine the importance of the language laboratory in modern teaching and to motivate teachers and executives to use it. The first part explains some common statements concerning a laboratory presenting its essential advantages, the several existing types, a summary of possible operations and respective student I teacher roles regarding the electronic apparatus. The second part clarifies the programming, production and exploitation of a sound laboratory - electronic library set. This summarized introduction to the language laboratory is done only from the audio point of view and it does not include a possible audio-visual integration under all desirable forms.